Median Lethal (LC50-48) with Azadirectha Biopestisides in Post Larva Tiger Shrimp (Penaeus monodon) in Low Salinity. Issue 1 (May 2021) - Septiningsih, E; Sahabuddin,; Permatasari, D
Abstract: The agricultural system in Indonesia is now more advanced by combining agriculture and fisheries on the same land, so research like this is carried out. This study aims to investigate the lethal concentration (LC50-48 hours) of the active ingredient biopesticide Azadirectha on tiger shrimp at the post-larvae stage, and to analyze the effect of Azadirectha biopesticide on the behavior of tiger prawn post larvae. The concentration of biopesticides used in the main test was determined from the results of 3 preliminary tests with an upper threshold value of 90, 000 ppm and a lower threshold value of 30, 000 ppm. Five biopesticide concentrations were used for the main test, i.e. 37, 372 ppm, 46, 555 ppm, 57, 994 ppm, 72, 244 ppm, 89, 994 ppm, and control. The data analysis technique for LC 50 uses probit analysis. The results obtained by the lethal concentration (LC50-48 hours) with Azadirectha biopesticide on mortality of tiger shrimp post-larvae were 54, 719.57 ppm, the effect of biopesticides on post larvae behavior of tiger prawns at a concentration of 40, 000 ppm only stayed at the bottom and even died while with a maximum biopesticide. At the concentration of 37, 372 ppm, the shrimp showed active behavior, making it a safe concentration limit for the shrimp to sustain a living.